Perspectives of adolescent and young adults on poverty-related stressors: a qualitative study in Ghana, Malawi and Tanzania - Hall, Brian J.; Garabiles, Melissa R.; de Hoop, Jacobus; Pereira, Audrey; Prencipe, Leah; Palermo, Tia (BMJ, 2019)
Objectives: To define key stressors experienced and coping behaviours within poor agrarian communities in sub-Saharan Africa.